2009
DOI: 10.1179/174328109x443347
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D X-ray tomography to investigation of structure of sinter mixture granules

Abstract: X-ray tomography was applied to the investigation of the structure of sinter mixture granules. Different components such as ore, concentrate, coke breeze and limestone were identified and their sizes and spatial distribution estimated. Classification of the granule structure by the thickness of the adhering fines layer in a proportion to the whole granule radius has been estimated. Excessive amount of fines (concentrate) in a mixture leads to the increasing presence of granules with an adhering fines layer thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 9 publications
(13 reference statements)
1
21
0
Order By: Relevance
“…In our previous work, 5 it was confirmed that following the well known granulation mechanism, 14 fine magnetite concentrate adheres to the coarse hematite ore or to the sinter return nuclei during granulation. According to Yang, 15 such granule's structure promotes oxidation of magnetite.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In our previous work, 5 it was confirmed that following the well known granulation mechanism, 14 fine magnetite concentrate adheres to the coarse hematite ore or to the sinter return nuclei during granulation. According to Yang, 15 such granule's structure promotes oxidation of magnetite.…”
Section: Resultsmentioning
confidence: 62%
“…5 It must be mentioned that X-ray tomography has been previously applied by other authors [6][7][8] to investigate a network of pores inside a sintered cake. These references are focused mainly on the permeability of the sintering bed in connection with the porosity of the cake.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the X-ray computed tomography (CT) technique has enabled researchers to study the three-dimensional (3D) microstructure of ferrous materials used in the ironmaking process, such as the porosity of sinter, granules and reduced pellet. [7][8][9][10] Nevertheless, to the knowledge of the authors, X-ray CT has never been used to examine the 3D structure of S&M samples. The high proportion of metallic iron ( > 50%) requires very high energy to penetrate the samples, i.e., normal laboratory scale CT scanners are not capable of penetrating the samples.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies (Shatokha et al, 2009(Shatokha et al, , 2010) a possibility to study the structure of sintering mixture granules and morphology of pores in the sintered product using 3D imaging technique, X-ray tomography, enabling non-destructive investigation of these complex heterogeneous materials, was demonstrated. In this research X-ray tomography technique was applied along with some other experimental methods to study microstructures of sinter granules and of sinter, and their relationship with the materials' properties.…”
Section: Introductionmentioning
confidence: 99%